Adherence to the diet with higher protein quality reduces the risk of colorectal cancer: results from a population-based prospective study - Feng, Dazhan; Wen, Ke; Xue, Junxia; Xiao, Yi; Gu, Haitao; Peng, Linglong; Luo, Yuxiang; Xiang, Ling; Wang, Yaxu; Liu, Dengliang (Frontiers in Nutrition, 2025)
BackgroundProtein quantity’s link to colorectal cancer (CRC) risk is known, but protein quality’s impact on US populations remains unclear. This study fills the gap via a population - based prospective study of 101,709 American adults from the PLCO Cancer Screening Trial.MethodsFrom 154,887 adults aged 55–74 years at 10 US screening centers, we formed the study group. HPPQI was calculated from the DHQ. Cox regression analysis determined HRs and 95% CIs for HPPQI - CRC associations. Subgroup and sensitivity analyses identified modifiers and ensured robustness.ResultsDuring the study period, 1100 CRC cases and 314 CRC-related deaths were documented. In our result, HPPQI was significantly negatively associated with incidence of CRC (HR Q4 vs. Q1: 0.77; 95% CI: 0.65, 0.93; P = 0.009 for trend), as well as mortality rate (HR Q4 vs. Q1: 0.66; 95% CI: 0.47, 0.91; P = 0.024 for trend). The relationships between HPPQI and the incidence and mortality of CRC were robustly supported by sensitivity analyses. Nevertheless, upon separate examination of the relationships between HPPQI and proximal colon cancer, distal colon cancer, and rectal cancer, none of these associations attained statistical significance (all P-values > 0.05).ConclusionOur findings suggest focusing on higher quality of protein consumption may be an effective approach to reduce the risk of CRC in the US population.